Analysis of Nursing Clinical Practice Using Ecoprint Occupational Therapy to Reduce Auditory Hallucination Symptoms - Lulu Khairiyah; Arief Budiman; Dwi Rahmah Fitriani; Linda Dwi Novial (Jurnal Kesehatan Cendikia Jenius, 2026)
Auditory hallucinations are a major symptom experienced by patients with schizophrenia and can disrupt cognitive, emotional, and social functioning, thus requiring comprehensive therapeutic management. This study is necessary because pharmacological therapy alone is not sufficient to optimize patients’ ability to control hallucinations, making meaningful non-pharmacological interventions essential. This study aimed to determine the effectiveness of ecoprint occupational therapy in reducing signs and symptoms of auditory hallucinations in Mr. I. The research employed a case study design involving one patient, with data collected using the Auditory Hallucination Rating Scale (AHRS), conducted over two consecutive days. The ecoprint intervention was implemented for approximately 60 minutes per session and analyzed descriptively. The results demonstrated a reduction in AHRS scores from 23 to 21 on the first day and from 17 to 11 on the second day, with improvements observed in frequency, intensity, negative voice content, disturbance to activities, and control over hallucinations. The patient also showed increased focus and engagement during the activity. In conclusion, ecoprint occupational therapy is effective as a supportive intervention for helping patients control auditory hallucinations. It is recommended for continued implementation with expanded duration and activity variations to enhance therapeutic outcomes.